Research and development of pulse electronic control devices with UV lamps - O. Yu. Kovalenko; S. A. Mikaeva; Yu. A. Zhuravleva (Российский технологический журнал, 2022)
Objectives. When used in lighting installations with tubular low-pressure ultraviolet (UV) lamps, electronic ballasts should meet the following basic requirements: low cost, reliable ignition at low temperatures, as well as combining high energy efficiency with reliable lamp operation. As compared with electromagnetic ballasts, electronic ballasts allow the luminous efficiency and power factor of discharge lamps to be increased, reducing the consumption of scarce materials along with the weight of devices. In order to improve their energy efficiency, complete UV lamps are based on low-pressure discharge lamps with pulsed electronic ballasts supplying power at the frequency of 22–50 kHz. Various circuit designs include such basic units as mains filter, rectifier, power factor corrector, smoothing filter, high-frequency converter, ballast, and ignition device. The present study aimed to develop an electronic semiconductor circuit for switching on and powering a discharge lamp of increased energy efficiency using a pulsed electronic ballast.Methods. Classical methods of mathematical research were applied for determining the flux of the 254-nm mercury resonance line using a structural electronic ballast diagram along with a mathematical description and adaptive model.Results. Equations for determining the parameters of pulses formed by an envelope having the form of input voltage and current supplied at industrial frequency were formulated for different instants of time. A mathematical description is given for determining pulse duration and lamp current depending on the values of nominal and operating voltage, as well as nominal current. Diagrams for instantaneous voltage values at the high-frequency switch input and generated pulsed current are presented. The parameters of the ‘UV lamp–electronic ballast’ set were calculated using an adaptive model for determining the flux of the 254-nm mercury resonance line according to the condition of lamp power constancy.Conclusions. Relative values for radiant efficiency of the 254-nm mercury line for UV lamps under study were determined. Theoretical research of electronic ballasts led to the development of a semiconductor switching and power supply circuit for the discharge lamp based on high-frequency rectangular pulses. The parameters of the element base were calculated along with selected basic initial characteristics of the blocking generator.